S-REST: A design of Secured Protocol for Implementation of RESTful Webservices - Subbalakshmi, Chatti; Sayal, Rishi; Saini, H.S (International Journal of Computer Sciences and Engineering, 2019)
Representational State Transfer (REST) is an architectural style for developing web services and its key constraints are Use of Uniform Interface (UI), client-server based, stateless operations, and Resource caching. It is popular due to its simplicity and builds on the existing systems. Hence, many cloud providers such as Amazon, Google are moving their APIs from Simple Object Access Protocol (SOAP) to REST. Unlike SOAP, RESTful service doesn’t provide standard for security while accessing web services. Hence, we considered the security issues in execution of RESTful web services and proposed a design of a secured model (S-Rest) over RESTful web services with 3-level security services at communication, Application and Management. The proposed architecture enhances the performance of RESTful web application